Differences in how leaders and employees view organizational changes: Lessons from an international multicultural context - Ghaith Al-Abdallah; Reda Helal; Ala' Omar Dandis; Len Tiu Wright (Cogent Business & Management, 2023)
The research aims to provide actionable insights to a Dubai-based digital payment company following a leadership-driven organizational transformation. Semi-structured interviews with executives and staff were supplemented by observations and field notes. The study found that foreign employees experienced confusion due to a lack of clear communication or information. Hierarchical work environments and legacy problems hindered employee change. Fear and distrust prevented employees from voicing their concerns. Employees and executives shared similar opinions on the work environment and organizational culture. Leaders did not place enough importance on early worker involvement, communication, and information flow, which hindered their vision and evaluation of employees' conduct. Earlier discussion and resolution of these issues may narrow the gap between the CEO and employees.
Keywords: 650; emerging markets; employees' engagement; employees' fear; employees' resistance; expat workforce; leadership change